Optimal recovery of heavy-oil using numerical simulation of polymer flooding - (:unkn) unknown (Slovnaft VURUP a.s, 2020)
These studies focused on polymer flooding for optimal recovery of heavy-oil. It was premised on a detailed reservoir simulation study using ECLIPSE and the polymer used was hydrolyzed polyacrylamide (HPAM). Water and polymer flooding cases were the scenarios considered. The water flooding case had its highest recovery with the "homogeneous case of low permeability" with a production total of 176412.3 sm3 (FOE=50.1 %). As for the polymer flooding cases, polymer concentrations in the range of 1 to 5 kg/m3 were tested. Polymer slugs with different concentrations at different injection times were injected for each case and the results were compared. The best polymer flooding case was with the use of HPAM of concentration 2.0 kg/m3 with 7 years of polymer injection followed by chase water injection. It had a recovery efficiency of over 84%. It also shows the most favorable reservoir pattern for polymer flooding in the heavy oil reservoir. © 2020 Slovnaft VURUP a.s.
Keywords: ECLIPSE; Heavy oil; Heterogeneous; Homogeneous; Polymer flooding; Recovery; Simulation